There is no way you can frame it. Ideias de Teatro e Cinema a partir de Michael Fried - Frazão, Francisco (MATLIT: Materialities of Literature, 2014)
Partindo do artigo "Art and Objecthood" (1967) de Michael Fried, analisam-se as ideias de teatro e cinema ali construídas, de forma a postular uma teatralidade cinematográfica imune ao preconceito antiteatral que muitas vezes carateriza os trabalhos sobre a interseção das duas artes. Dado o lugar tangencial do cinema em "Art and Objecthood", recorre-se a outros textos (muitos do mesmo período e sobretudo da linhagem dos Cahiers du Cinéma) para desmontar a ideia de cinema de Fried e fazer emergir uma nova. Duas cenas, uma de Godard e outra de Tsai Ming-liang, são usadas para exemplificar a teatralidade proposta. Abstract I analyze the concepts of theatre and film in Michael Fried's "Art and Objecthood" (1967), in order to argue for a cinematic theatricality immune to the anti-theatrical prejudice often found in works about the intersection of these two art forms. Given the tangential place of movies in Fried's article, other texts are used (mostly from the same period and mainly from the Cahiers du Cinéma tradition) to deconstruct Fried's idea of film so that a new concept can emerge. Two scenes, one from Godard and the other from Tsai Ming-liang, are used to illustrate the proposed theatricality. DOI: http://dx.doi.org/10.14195/2182-8830_1-2_6